PEMBANGUNAN GENERASI MUDA DALAM PANDANGAN FORUM GENRE, DUTA GENRE DAN PEMERINTAH DAERAH - Lusiana Fahrudin, Swastika; Azijah, Dewi Noor; Rizki, Moch. Faisal (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
This study aims to understand the views of the Planning Generation Forum (GenRe), GenRe Ambassadors, and the Regional Government in the development of the youth generation in Indonesia. With a qualitative approach, data collection was conducted through in-depth interviews with representatives from the three parties. The analysis was conducted using the perspective of youth development theory, Sustainable Development Goals (SDGs), and the Planning Generation Program. The results of the study show that the three parties have a shared vision in building a quality, healthy, and empowered young generation. The GenRe Forum acts as a space for communication, education, and capacity development for youth. GenRe Ambassadors act as agents of change who provide positive influences through a peer approach. Meanwhile, the Regional Government contributes by providing facilities, policies, and budget support to ensure the sustainability and effectiveness of the GenRe program. The collaboration of the three is key to realizing inclusive and sustainable youth development.